2003
DOI: 10.1021/om034148d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Fluorinated Aminoalkoxide and Iminoalkoxide Gallium Complexes:  Application in Chemical Vapor Deposition of Ga2O3 Thin Films

Abstract: Gallium trichloride, GaCl 3 , reacts with the in situ prepared sodium salt of an aminoalkoxide or iminoalkoxide, denoted as NaL, to give the disubstituted compounds GaL 2 Cl, where L ) OC(CF 3 ) 2 CH 2 NMe 2 (1), OC(CF 3 ) 2 CH 2 C(Me)dNMe (2). Single-crystal X-ray diffraction studies on 1 and 2 indicated the formation of a trigonal-bipyramidal structure with chloride and alkoxy groups occupying the equatorial sites and the nitrogen donors located at the axial positions. For the related trimethylgallium reagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 36 publications
4
39
0
Order By: Relevance
“…100 39 They also used the metathesis reaction of the sodium salt of fluorinated aminoalcohol [HOC(CF 3 ) 2 CH 2 NMe 2 (Hamak F )] and iminoalcohol [HOC(CF 3 ) 2 CH(Me)NMe (Himak F )] with GaCl 3 in diethyl ether to prepare the bis complexes [Ga(amak F ) 2 Cl] and [Ga(imak F ) 2 Cl]. 42 In contrast, the reactions of same ligands with trimethylgallium afforded only the monosubstituted complexes [GaMe 2 (amak F )] and [GaMe 2 (imak F )]. 42 On the other hand, complete halide removal was possible in the reactions of MX 4 [M = Ti (X = F), Zr (X = Cl)] with Li/Na salts of hexafluorophenyltertiarybutanol or a tetradentate β-diketoimine, 101 However, the reactions proceeds with the formation of water as a byproduct to give sometimes hydrated metal complexes.…”
Section: Synthetic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…100 39 They also used the metathesis reaction of the sodium salt of fluorinated aminoalcohol [HOC(CF 3 ) 2 CH 2 NMe 2 (Hamak F )] and iminoalcohol [HOC(CF 3 ) 2 CH(Me)NMe (Himak F )] with GaCl 3 in diethyl ether to prepare the bis complexes [Ga(amak F ) 2 Cl] and [Ga(imak F ) 2 Cl]. 42 In contrast, the reactions of same ligands with trimethylgallium afforded only the monosubstituted complexes [GaMe 2 (amak F )] and [GaMe 2 (imak F )]. 42 On the other hand, complete halide removal was possible in the reactions of MX 4 [M = Ti (X = F), Zr (X = Cl)] with Li/Na salts of hexafluorophenyltertiarybutanol or a tetradentate β-diketoimine, 101 However, the reactions proceeds with the formation of water as a byproduct to give sometimes hydrated metal complexes.…”
Section: Synthetic Methodsmentioning
confidence: 99%
“…42 In contrast, the reactions of same ligands with trimethylgallium afforded only the monosubstituted complexes [GaMe 2 (amak F )] and [GaMe 2 (imak F )]. 42 On the other hand, complete halide removal was possible in the reactions of MX 4 [M = Ti (X = F), Zr (X = Cl)] with Li/Na salts of hexafluorophenyltertiarybutanol or a tetradentate β-diketoimine, 101 However, the reactions proceeds with the formation of water as a byproduct to give sometimes hydrated metal complexes. These hydrated complexes are, however, unattractive for the materials processing due to the uncontrolled reactivity, which water molecules may introduce in the precursor solution.…”
Section: Synthetic Methodsmentioning
confidence: 99%
“…17 Gallium derivatives Ga{OL} 2 Cl, where LO = OC(CF 3 ) 2 -CH 2 NMe 2 , OC(CF 3 ) 2 CH 2 C(Me)=NMe, were similarly prepared from GaCl 3 and the corresponding ligand sodium salt (Scheme 10). 20 Single-crystal X-ray diffraction studies revealed mononuclear compounds in a trigonal-bipyramidal (tbp) geometry with chloride and alkoxy groups occupying the equatorial sites and the nitrogen donors located at the axial positions. Methane elimination reactions from GaMe 3 and one equivalent of fluorinated amino-alcohol LOH (LO = OC(CF 3 ) 2 CH 2 NRR¢ with R = H, R¢ = Me, tBu, R = R¢ = Me) proceeded in high yields to afford the GaMe 2 {OL} complexes (Scheme 10).…”
Section: Late Transition and Main Group Metal Complexes Based On Iminmentioning
confidence: 99%
“…Interest in these compounds, particularly with internally functionalized ligands, appears to be due to their wide structural diversity [1], potential applications as catalyst [4,5] as well as molecular precursors for the preparation of metal oxide thin films [6][7][8] and photophysical properties [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%